Transformation of Endophytic Bipolaris spp. Into Biotrophic Pathogen Under Auxin Cross-Talk With Brassinosteroids and Abscisic Acid - Yousaf, Muhammad Junaid; Hussain, Anwar; Hamayun, Muhammad; Iqbal, Amjad; Irshad, Muhammad; Kim, Ho-Youn; Lee, In-Jung (Frontiers in Bioengineering and Biotechnology, 2021)
Auxin is the reciprocal signalling molecule, which interferes with other phyto-hormonal and physiological processes during plant-microbes interaction. In this regard, Bipolaris spp. a growth promoting endophytic fungus was used to inoculate pre-stressed Zea mays seedlings with yucasin (IAA inhibitor). The IAA deficient host was heavily colonized by the endophyte that subsequently promoted the host growth and elevated the IAA levels with a peak value at 72 h. However, the seedling growth was inhibited later (i.e. 120 h) due to the high levels of IAA that interfered with the activity of phytoalexins and brassinosteroids. Such interference also modulated the endophytic fungus from symbiotic to biotrophic pathogen that left the host plants defenseless.